GE_GERICHTE C/1929/2004 vom 5. September 2017 - GE Cour de justice (2017)
OBLIGATION D'ENTRETIEN ; TRANSACTION(ACCORD) ; AUTORISATION OU APPROBATION(EN GÉNÉRAL) ; COMPÉTENCE | CC.276; CC.285; CC.287.1; LACC.5.3.E